Increased Production of Recombinant O-Phospho-L-Serine Sulfhydrylase from the Hyperthermophilic Archaeon Aeropyrum pernix K1 Using Escherichia coli - Nakamura, Takashi; Takeda, Emi; Kiryu, Tomoko; Mori, Kentaro; Ohori, Miyu; Kikugawa, Eiki; Ishikawa, Kazuhiko (Current Biotechnology, 2019)
Background: O-phospho-L-serine sulfhydrylase from the hyperthermophilic archaeon Aeropyrum pernix K1 (ApOPSS) is thermostable and tolerant to organic solvents. It can produce nonnatural amino acids in addition to L-cysteine. Objective: We aimed to obtain higher amounts of ApOPSS compared to those reported with previous methods for the convenience of research and for industrial production of L-cysteine and non-natural amino acids. Methods: We performed codon optimization of cysO that encodes ApOPSS, for optimal expression in Escherichia coli. We then examined combinations of conditions such as the host strain, plasmid, culture medium, and isopropyl β-D-1-thiogalactopyranoside (IPTG) concentration to improve ApOPSS yield. Results and Discussion: E. coli strain Rosetta (DE3) harboring the expression plasmid pQE-80L with the codon-optimized cysO was cultured in Terrific broth with 0.01 mM IPTG at 37°C for 48 h to yield a 10-times higher amount of purified ApOPSS (650 mg·L-1) compared to that obtained by the conventional method (64 mg·L-1). We found that the optimal culture conditions along with codon optimization were essential for the increased ApOPSS production. The expressed ApOPSS had a 6-histidine tag at the N-terminal, which did not affect its activity. This method may facilitate the industrial production of cysteine and non-natural amino acids using ApOPSS. Conclusion: We conclude that these results could be used in applied research on enzymatic production of L-cysteine in E. coli, large scale production of non-natural amino acids, an enzymatic reaction in organic solvent, and environmental remediation by sulfur removal.
Keywords: terrific broth